Metal concentrations in sediments from tourist beaches of Miri City, Sarawak, Malaysia (Borneo Island) - Ramasamy, Nagarajan; M. P. Jonathan; Roy, Priyadarsi; Wai-Hwa, L.; Prasanna, Mohan Viswanathan; Sarkar, S.K.; Navarrete-Lopez, M. (Elsevier, 2013)
Forty-three sediment samples were collected from the beaches of Miri City, Sarawak, Malaysia to identify the enrichment of partially leached trace metals (PLTMs) from six different tourist beaches. The samples were analyzed for PLTMs Fe, Mn, Cr, Co, Cu, Ni, Pb, Sr and Zn. The concentration pattern suggest that the southern side of the study area is enriched with Fe (1821–6097 μg g−1), Mn (11.57–90.22 μg g−1), Cr (51.50–311 μg g−1), Ni (18–51 μg g−1), Pb (8.81–84.05 μg g−1), Sr (25.95–140.49 μg g−1) and Zn (12.46–35.04 μg g−1). Compared to the eco-toxicological values, Cr > Effects range low (ERL), Lowest effect level (LEL), Severe effect level (SEL); Cu > Unpolluted sediments, ERL, LEL; Pb > Unpolluted sediments and Ni > ERL and LEL. Comparative results with other regions indicate that Co, Cr, Cu, Ni and Zn are higher, indicating an external input rather than natural process.